KEBIJAKAN PENGHAPUSAN IZIN LINGKUNGAN DALAM RUU CIPTA KERJADAN DAMPAKNYATERHADAP PEMBANGUNAN BERKELANJUTANDI INDONESIA - Benuf, Kornelius; Aritonang, Abram Robert; Simanjuntak, Supriardoyo (UI Scholars Hub, 2021)
The government is currently discussing about Jobs Creation Bill on the implementation of national development. The drafting of Jobs Creation Bill is carriedout by applying the omnibus law system. However, on the Bill there are numbers of irregularities such as the removal of environmental permits and replaced with environmental agreements. This raises legal issues because the changes of terminology onthe Bill have juridical implications for the implementations of sustainable developments in Indonesia. This legal issue will be researched further in this study. The method used is normative juridical with secondary data in the form of primary legal materials ofthe Jobs Creation Bill and secondary legal materials such as related literature. Result of the study concluded that the granting of environmental approval as a substitute for the permits to continue carry out environmental feasibility test to meet UKL-UPLstandards and PKPLH issuance. In addition, the central government can impose administrative penalty such as fines to entrepreneurs who do not have environmental agreement or who do not carry out their obligations.